2016
DOI: 10.1073/pnas.1604921113
|View full text |Cite
|
Sign up to set email alerts
|

Key experimental evidence of chromosomal DNA transfer among selected tuberculosis-causing mycobacteria

Abstract: Horizontal gene transfer (HGT) is a major driving force of bacterial diversification and evolution. For tuberculosis-causing mycobacteria, the impact of HGT in the emergence and distribution of dominant lineages remains a matter of debate. Here, by using fluorescenceassisted mating assays and whole genome sequencing, we present unique experimental evidence of chromosomal DNA transfer between tubercle bacilli of the early-branching Mycobacterium canettii clade. We found that the obtained recombinants had receiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
79
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 101 publications
(86 citation statements)
references
References 43 publications
3
79
0
Order By: Relevance
“…In the MTBC, M. canettii is most closely related to the vanished ancestor (1)(2)(3)(4)(5). M. canettii is uniquely characterized by a large (4.48 Ϯ 0.05 Mb) and mosaic genome with traces of intraspecies horizontal gene transfer (HGT) (3,5,6), including M. tuberculosis-specific deletion 1 (TbD1), which is deleted in "modern" M. tuberculosis lineages (7). In culture, M. canettii appears as large and cordless mycobacteria, and it forms smooth colonies (3,8,9).…”
mentioning
confidence: 99%
“…In the MTBC, M. canettii is most closely related to the vanished ancestor (1)(2)(3)(4)(5). M. canettii is uniquely characterized by a large (4.48 Ϯ 0.05 Mb) and mosaic genome with traces of intraspecies horizontal gene transfer (HGT) (3,5,6), including M. tuberculosis-specific deletion 1 (TbD1), which is deleted in "modern" M. tuberculosis lineages (7). In culture, M. canettii appears as large and cordless mycobacteria, and it forms smooth colonies (3,8,9).…”
mentioning
confidence: 99%
“…In support of these findings, a recent study by Boritsch et al indicated that a similar process of horizontal gene transfer was observed in Mycobacterium canettii, a close relative of M. tuberculosis. Although the dependence of the observed DNA transfer on the ESX-1 and ESX-4 systems was not tested, this study indicates that horizontal gene transfer is likely widespread in mycobacteria (69).…”
mentioning
confidence: 83%
“…These genes may be localized in different genomic positions in the various mycobacterial species concerned. The molecular tools that have helped to establish these putative ancestral horizontal transfer events of the espACD operons into slow‐growing mycobacterial species are unknown, but could have involved recently identified plasmid‐mediated (Dumas et al ., ) and/or chromosomal mycobacterial DNA transfer mechanisms (Boritsch et al ., ).…”
Section: Featured Opinionmentioning
confidence: 97%